2002
DOI: 10.1364/josaa.19.001951
|View full text |Cite
|
Sign up to set email alerts
|

Variations in normal color vision III Unique hues in Indian and United States observers

Abstract: Basic color categories are thought to share a common pattern across linguistic groups, yet the focal colors defining those categories can vary substantially within any single group. We asked whether focal colors can also differ systematically across different groups of individuals living in potentially different color environments, by measuring focal and unique hues for observers in India and the United States. Differences between groups were generally small relative to the within-group variations, consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 26 publications
5
53
1
Order By: Relevance
“…According to the author, this would support the hypothesis of a neurophysiological basis for the perceptual mechanisms guiding foci localization, that would dominate over cultural influences. These findings are in agreement with those of Webster et al (2002). In their experiment, they addressed the question whether focal colors can differ systematically across different groups of individuals living in potentially different color environments.…”
Section: Rationalesupporting
confidence: 72%
See 1 more Smart Citation
“…According to the author, this would support the hypothesis of a neurophysiological basis for the perceptual mechanisms guiding foci localization, that would dominate over cultural influences. These findings are in agreement with those of Webster et al (2002). In their experiment, they addressed the question whether focal colors can differ systematically across different groups of individuals living in potentially different color environments.…”
Section: Rationalesupporting
confidence: 72%
“…This would allow checking the crosscultural coherence assumption, namely if cross-linguistic differences do have any impact on color categorization. However, we assume here that between-cultural differences are comparable to within group variations (Kuehni, 2005;Webster et al, 2002).…”
Section: Rationalementioning
confidence: 99%
“…In fact, if anything, it is the Berinmo data that would dispute their hypothesis as they live in lowland dense forest that sunlight does not easily penetrate. However, in a recent investigation, Webster et al, (2002) showed systematic differences in the location of unique yellow judgments, in the absence of color-vision defects, within a population living in an equatorial region (India). These differences were attributed to cultural constraints (one population was composed of cloth factory workers who use particular shades of yellow thread) as the sunlight (UVB) exposure was equated for both groups (see also Hardy et al, in press).…”
Section: Color Categories 38mentioning
confidence: 94%
“…26 In this study we examined the structure of color appearance by observing individual differences in color naming. Subjects with normal color vision have been previously shown to vary widely in the stimuli they select for the unique hues 10,[27][28][29][30][31] and in the focal stimuli they select for basic color terms. 18,21,22,31 Thus a yellow that appears distinctly reddish to one observer might appear strongly greenish to another.…”
Section: Introductionmentioning
confidence: 99%